Effect of Substrate Temperature on the Structural, Optical and Surface Properties of Aluminium Doped Cadmium Sulphide Thinfilms - Rajathi1, S.; Sankara Subramanian1, N.; Ramanathan2, K.; Senthamizhselvi1, M.; Shanmugam3, S. (Asian Journal of Chemistry, 2013)
Aluminium doped cadmium sulphide (CdAlS) thin films were prepared by spray pyrolysis method at different substrate temperature. The XRD profile of the films illustrates the hexagonal structure with the preferred orientation along the (002) plane. The lattice constant a and c have been evaluated as 4.123 Å and 6.6747 Å from the XRD data. The crystallographic parameters viz., average grain size, lattice strain and dislocation density, texture coefficient and standard deviation have been calculated from the experimentally observed XRD data. The average crystallite size calculated from the XRD data lies between 120 to 375 nm. The effect of substrate temperature on the optical properties of the films viz., extinction coefficient, absorption coefficient has been calculated from the transmittance data measured in the UV-visible region. The direct band gap energy of the CdAlS thinfilms evaluated from the transmittance measurement lies between 2.25 eV to 3.25 eV. The surface properties viz., surface roughness and grain size have been investigated from the SEM micrograph.